Sanskrit Grammar : Including Both the Classical Language, and the Older Dialects, of Veda and Brahmana - Whitney, William Dwight, (Brill | Manohar Publishers & Distributors, 2024)
Similar to Phoenician, Babylonian, ancient Greek and Tamil, Sanskrit too has an advanced grammar system. Panini was noted as one of the world's first grammarians who composed the rules of grammar, which itself is an achievement. This book, Sanskrit Grammar, is for learning Classical Sanskrit for beginners to advanced level. It contains basic and advanced grammar rules such as alphabets, numerical systems, sounds, vowels-consonants, nouns, adjectives, declensions, conjugations, compound stems, and so forth. The book was compiled with the help of sources such as Vedas, Upanishads, Epics, Brahmanas, and numerous classical Sanskrit compositions. Highly beneficial for students who want to learn the Sanskrit language.